2015
DOI: 10.3390/ma8125465
|View full text |Cite
|
Sign up to set email alerts
|

On the Passivity of Hysteretic Systems with Double Hysteretic Loops

Abstract: The Bouc–Wen hysteresis model is widely employed to mathematically represent the dynamical behavior of several physical devices, materials and systems such as magnetorheological dampers, lanthanide zirconium or aluminum oxides, mechanical structures or biomedical systems. However, these mathematical models must account for different properties such as the bounded-input bounded-output stability, asymptotic motion, thermodynamic admissibility or passivity in order to be physically consistent with the systems the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…8 illustrates this weighting function with the region Ω c indicated by a dashed line. It follows that the hysteresis loop obtained from a Preisach operator with a weighting function µ defined by (20) and whose input u has one maximum u max = β 1 and one minimum u min = −β 1 has a crossover point with coordinates (u c , y c ) = (0, 0), where y c is computed using ( 16) or (17). Nevertheless, by simple inspection of the phase plot include in Fig.…”
Section: Preisach Multi-loop Operatormentioning
confidence: 99%
See 2 more Smart Citations
“…8 illustrates this weighting function with the region Ω c indicated by a dashed line. It follows that the hysteresis loop obtained from a Preisach operator with a weighting function µ defined by (20) and whose input u has one maximum u max = β 1 and one minimum u min = −β 1 has a crossover point with coordinates (u c , y c ) = (0, 0), where y c is computed using ( 16) or (17). Nevertheless, by simple inspection of the phase plot include in Fig.…”
Section: Preisach Multi-loop Operatormentioning
confidence: 99%
“…Using Lemma 4.3 with the region Ω α1 defined in (21), the hysteresis loop H u,y has a crossover point (u c , y c ) with u c = u(τ 1 ) = u(τ 2 ) = α 1 and where y c = y(τ 1 ) = y(τ 2 ) is given by ( 16) or (17).…”
Section: Preisach Multi-loop Operatormentioning
confidence: 99%
See 1 more Smart Citation
“…First, in [22], a modified Bouc-Wen is studied, which can describe a particular class of asymmetric double hysteresis loop behavior by introducing position and/or acceleration information into the model equation. Moreover, when the parameters of the model satisfy particular conditions, it has been shown that passivity property holds [23]. Second, in [24], a framework to transform butterfly loops to single-oriented loops is proposed.…”
Section: Introductionmentioning
confidence: 99%
“…It was validated using a magnetostrictive actuator system. Another approach for modeling butterfly hysteresis behavior relies on a modified Bouc-Wen model [58,59] which incorporates either acceleration or position information. Numerical simulations have been performed to validate the framework.…”
Section: Hysteresis Models For Asymmetric Butterfly Loopsmentioning
confidence: 99%